Finite Sums Involving Reciprocals of the Binomial and Central Binomial Coefficients and Harmonic Numbers - Necdet Batir (MDPI AG, 2021)
We prove some finite sum identities involving reciprocals of the binomial and central binomial coefficients, as well as harmonic, Fibonacci and Lucas numbers, some of which recover previously known results, while the others are new.